1995
DOI: 10.1128/mcb.15.12.6694
|View full text |Cite
|
Sign up to set email alerts
|

M-Phase-Specific Phosphorylation of the POU Transcription Factor GHF-1 by a Cell Cycle-Regulated Protein Kinase Inhibits DNA Binding

Abstract: GHF-1 is a member of the POU family of homeodomain proteins. It is a cell-type-specific transcription factor responsible for determination and expansion of growth hormone (GH)-and prolactin-expressing cells in the anterior pituitary. It was previously suggested that cyclic AMP (cAMP)-responsive protein kinase A (PKA) phosphorylates GHF-1 at a site within the N-terminal arm of its homeodomain, thereby inhibiting its binding to the GH promoter. These results, however, are inconsistent with the physiological stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 40 publications
(77 reference statements)
1
61
1
Order By: Relevance
“…The phosphoacceptor residue, Thr-220 is located into the POU homeodomain. These results could not be confirmed in cultured cells (58). However, the Thr-220 is transiently phosphorylated during mitosis by a mitosis-specific kinase.…”
Section: Autoregulation Of Human Pit1/ghf1 Gene Expression-contrasting
confidence: 43%
See 1 more Smart Citation
“…The phosphoacceptor residue, Thr-220 is located into the POU homeodomain. These results could not be confirmed in cultured cells (58). However, the Thr-220 is transiently phosphorylated during mitosis by a mitosis-specific kinase.…”
Section: Autoregulation Of Human Pit1/ghf1 Gene Expression-contrasting
confidence: 43%
“…However, the Thr-220 is transiently phosphorylated during mitosis by a mitosis-specific kinase. This results in a transient decrease of the Pit-1/GHF-1 DNA binding activity during the M phase of the cell cycle (58). Therefore, a possible function for the TRE could be to mediate a complete transcriptional shut-off of the human PIT1/GHF1 gene when the DNA binding activity of the Pit-1/GHF-1 protein is inhibited by mitotic phosphorylation.…”
Section: Autoregulation Of Human Pit1/ghf1 Gene Expression-mentioning
confidence: 99%
“…Among this family, Ikaros and Sp1 are not only excluded from chromatin in early mitosis, but it has also been shown that the three linkers of Ikaros and at least one of the Sp1 linkers are phosphorylated [Dovat et al, 2002]. Similarly, the DNA-binding ability of Oct-1 and GHF-1, two members of the POU family, is lost upon mitotic phosphorylation of the same conserved amino acid of the POU domain [Segil et al, 1991;Caelles et al, 1995]. These findings imply that mitotic inactivation of transcription factors through phosphorylation may be a mechanism common to every family of transcription factors.…”
Section: Spatial Mitotic Reorganization Exclusion Of Transcription-asmentioning
confidence: 98%
“…Although the mechanism for Ras stimulation of the Pit-1 R2 TAD has yet to be elucidated, we know that in Ets-1 the Thr-82 MAP kinase phosphorylation site is required for Ras responsiveness because mutation of this site to an alanine blocks the ability of Ets-1 to enhance the Ras response (10,14). There are potential phosphorylation sites within the Pit-1 TAD, but none of them is a proline-directed MAP kinase site, and to date only serine 115 and threonines 219 and 220 have been shown to be phosphorylated by various signaling pathways and kinases (47,48), suggesting that Ras activation of the amino-terminal Pit-1 TAD is not mediated through direct phosphorylation of the TAD. Thus, the R2 subregion represents a novel and tissuespecific Ras-regulated TAD.…”
Section: Pit-1 Monomer Versus Dimer Dna Binding Sites Are Not a Primamentioning
confidence: 99%